Tuntutan Akuntabilitas Masyarakat terhadap Pemerintah atas Pajak dan dan Retribusi - Surifah - (Unisia, 2007)
The several criticisms toward the accountability of the govemment in term of tax policy either in its legislation, tax act or the implementation of tax legislation. There are many problems in this context, for instance unqualified human resources, the benefit of tax that not transparancy yet. Accountability that needed by society should be conducted by the government and constituted the rights of society to accept. The efforts that have been done by government to increase the accountability is still needs work hard and involving many parts of society so that be more efficiency and effectivity.